Factors Predicting Health Literacy in Older Persons with Type 2 Diabetes Mellitus - Manasaksirikul, Thipvimol; Wirojratana, Virapan; Wattanakijkrilert, Doungrut (Nursing Science Journal of Thailand, 2024)
Purpose: To investigate predictability of selected factors including age, gender, education, income, visual acuity and family support on health literacy in older persons with type 2 diabetes mellitus. Design: Correlational predictive research. Method: Participants were 146 older persons with type 2 diabetes mellitus aged 60 years and older who met the inclusion criteria and attended the outpatient department at a tertiary care hospital. Data were collected using demographic data, health literacy in older persons with type 2 diabetes and family support questionnaires. Data were analyzed by using descriptive statistics and multiple regression analysis. Main findings: The results showed that all of the independent variables could account for 79.4% of the variance explained in health literacy in older persons with type 2 diabetes (adj R2 = .79). Family support ( = .50, p < .001), education ( = .30, p < .001) and visual acuity ( = .24, p < .001) were statistically significant predictors of health literacy in older persons with type 2 diabetes mellitus while age, gender and income were not. Conclusion and recommendations: Family support, education and visual acuity were predictive factors of older persons with type 2 diabetes mellitus. Thus, the health care team should take screening assessments of education level and visual acuity to provide an appropriate activity in conjunction with accessing the level of family support to encourage family involvement in health activities to enable older persons with type 2 diabetes mellitus to develop their health literacy effectively.